Collective decision making reduces metacognitive control and increases error rates, particularly for overconfident individuals. (5th January 2020) - Blanchard, Matthew D.; Jackson, Simon A.; Kleitman, Sabina
Abstract: This research aimed to investigate the changes in judgment accuracy, confidence, control thresholds, and decision outcomes when people act in two‐person groups (dyads) compared with acting individually. First, we used interacting dyads to determine the metacognitive and behavioral outcomes of collective decision making and compared them with those of individuals. Second, we examined whether these changes were related to the trait‐confidence and bias of individuals working together. Using a within‐person design, undergraduate psychology students ( N = 116) completed a General‐knowledge Test individually, then together as a dyad. Each question was accompanied by a confidence rating and a decision to bet $10 on the answer. Dyads had significantly higher confidence and lower control thresholds than individuals. They were also significantly more decisive (made more bets) and reckless (lost a higher rate of bets) than when working alone. Thus, we observed a higher rate of decision errors for groups than individuals. The results also demonstrated the important role of individual differences: Overconfident individuals became even more confident, decisive, and reckless when working together compared with less confident or underconfident individuals working together. These findings have important theoretical and applied implications for collective decision making; metacognitive bias and potentially control thresholds may be targeted to alleviate the larger error rates and guide the formation of more effective groups.